ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NAFSU MAKAN PADA PASIEN DENGAN PENYAKIT PERNAFASAN OBSTRUKTIF KRONIS DI RSUD DR.M.SOEWANDHIE SURABAYA - ., Tjahjono, Sitorus, Sabri (S1 Keperawatan, 2012)
The relevance of lung disease and nutrition are important aspects of patient care. Patients nutritional problems associated with Chronic Obstructive Respiratory Disease (COPD) are complex, loss weight as a consequence of decreased food intake and appetite. The research aimed to get an idea of the factors that affected appetite. The research was a descriptive analytic cross sectional design within 75 people as sample in Dr.M.Soewandhie Surabaya hospital. The instruments of respondent characteristics questionnaire, medication observed, family supported and appetite were used. This research concluded that 65,3% from 75 COPD patients had poor appetite. The determinant variable related to appetite was family support, the patient who had family support decreased would be have 3,44 times poor appetite. According to attain a certain aimed, increased of family support necessary passed through within health education and dietary counseling to nutritional maintenance in COPD patients.Key words: COPD, family support, appetite